The Relationship Between Self-Control and Cyberbullying Behavior among Generation Z Users of X - Faradisa Faradisa; Iqmal Wahyudi (Program Studi Bimbingan dan Konseling Islam, 2026)
yberbullying has become an increasingly serious problem in digital communication, particularly among young social media users. This study aims to examine the relationship between self-control and cyberbullying behavior among Generation Z users of X. This research employed a quantitative approach with a correlational design. The sample consisted of 347 Generation Z respondents who actively used X and resided in City X, selected through purposive sampling. Data were collected using a self-control scale based on Averill’s theory and a cyberbullying behavior scale based on Willard’s theory. The data were analyzed using Pearson’s product-moment correlation. The results showed a significant negative relationship between self-control and cyberbullying behavior, with a correlation coefficient of -0.281 and a significance value of 0.000. The coefficient of determination indicated that self-control explained approximately 7.9% of the variance in cyberbullying behavior, while the remaining 92.1% may be influenced by other factors. These findings suggest that higher self-control is associated with lower cyberbullying behavior among Generation Z users of X. However, cyberbullying behavior is a complex phenomenon that cannot be explained by self-control alone. Therefore, cyberbullying prevention efforts should also consider other factors, such as emotional regulation, empathy, peer influence, digital literacy, online disinhibition, and social media use intensity.